Vitamin C and Doxycycline: A synthetic lethal combination therapy targeting metabolic flexibility in cancer stem cells (CSCs) - De Francesco, Ernestina Marianna; Bonuccelli, Gloria; Maggiolini, Marcello; Sotgia, Federica; Lisanti, Michael P (Oncotarget, 2017)
Here, we developed a new synthetic lethal strategy for further optimizing the eradication of cancer stem cells (CSCs). Briefly, we show that chronic treatment with the FDA-approved antibiotic Doxycycline effectively reduces cellular respiration, by targeting mitochondrial protein translation. The expression of four mitochondrial DNA encoded proteins (MT-ND3, MT-CO2, MT-ATP6 and MT-ATP8) is suppressed, by up to 35-fold. This high selection pressure metabolically synchronizes the surviving cancer cell sub-population towards a predominantly glycolytic phenotype, resulting in metabolic inflexibility. We directly validated this Doxycycline-induced glycolytic phenotype, by using metabolic flux analysis and label-free unbiased proteomics. Next, we identified two natural products (Vitamin C and Berberine) and six clinically-approved drugs, for metabolically targeting the Doxycycline-resistant CSC population (Atovaquone, Irinotecan, Sorafenib, Niclosamide, Chloroquine, and Stiripentol). This new combination strategy allows for the more efficacious eradication of CSCs with Doxycycline, and provides a simple pragmatic solution to the possible development of Doxycycline-resistance in cancer cells. In summary, we propose the combined use of i) Doxycycline (Hit-1: targeting mitochondria) and ii) Vitamin C (Hit-2: targeting glycolysis), which represents a new synthetic-lethal metabolic strategy for eradicating CSCs. This type of metabolic Achilles' heel will allow us and others to more effectively "starve" the CSC population.